2018
DOI: 10.1128/jvi.01099-18
|View full text |Cite
|
Sign up to set email alerts
|

Type I Interferon Signaling Prevents Hepatitis B Virus-Specific T Cell Responses by Reducing Antigen Expression

Abstract: Robust virus-specific CD8 T cell responses are required for the clearance of hepatitis B virus (HBV). However, the factors that determine the magnitude of HBV-specific CD8 T cell responses are poorly understood. To examine the impact of genetic variations of HBV on HBV-specific CD8 T cell responses, we introduced three HBV clones (Aa_IND [Aa], C_JPN22 [C22], and D_IND60 [D60]) that express various amounts of HBV antigens into the livers of C57BL/6 (B6) (H-2b) mice and B10.D2 (H-2d) mice. In B6 mice, clone C22 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…In summary, we have demonstrated that ISG expression is selectively suppressed in have been previously described (7,31). Over 98% of the splenic CD8 + T cells of COR93 TCR-Tg mice recognize a Kb-restricted epitope located between residues 93 and 100 in the HBcAg (MGLKFRQL), while approximately 83% of the splenic CD8 + T cells of ENV28 TCR-Tg mice recognize an Ld-restricted epitope located between residues 28 and 39 of the HBsAg (IPQSLDSWWTSL).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In summary, we have demonstrated that ISG expression is selectively suppressed in have been previously described (7,31). Over 98% of the splenic CD8 + T cells of COR93 TCR-Tg mice recognize a Kb-restricted epitope located between residues 93 and 100 in the HBcAg (MGLKFRQL), while approximately 83% of the splenic CD8 + T cells of ENV28 TCR-Tg mice recognize an Ld-restricted epitope located between residues 28 and 39 of the HBsAg (IPQSLDSWWTSL).…”
Section: Discussionmentioning
confidence: 52%
“…In all experiments, the HBV-Tg and B6 mice were matched for age (8–10 weeks), sex (male), and serum hepatitis B e antigen levels in HBV-Tg mice before experimental manipulation. COR93 TCR-Tg mice (lineage BC10.3, inbred CD45.1, H-2b) and ENV28 TCR-Tg mice (lineage 6C2.16, inbred Thy1.1 BALB/c, H-2d) have been previously described ( 7 , 31 ). Over 98% of the splenic CD8 + T cells of COR93 TCR-Tg mice recognize a Kb-restricted epitope located between residues 93 and 100 in the HBcAg (MGLKFRQL), while approximately 83% of the splenic CD8 + T cells of ENV28 TCR-Tg mice recognize an Ld-restricted epitope located between residues 28 and 39 of the HBsAg (IPQSLDSWWTSL).…”
Section: Methodsmentioning
confidence: 99%
“…HBV-specific CD8 + CTLs can mediate the killing of the infected hepatocytes and accelerate the clearance of cccDNA. Nevertheless, the HBV-specific CTLs can be deleted or dysfunctional or succumb to exhaustion in patients with chronic HBV infection ( Benechet and Iannacone, 2017 ; Kawashima et al., 2018 ). Moreover, recent studies showed that priming by hepatocytes, CD8 + T cells differentiated into dysfunctional HBV-specific CTLs, with partial overlap with those of exhausted or tolerant T cells; thus, these HBV-specific CTLs could not be rescued by treatment with immune checkpoint inhibitors such as anti-PD-L1 or CD40-mediated myeloid dendritic cells (mDCs)-activation ( Benechet et al., 2019 ; Isogawa et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…But after the adoptive cell transfer, the premature lymphocytes might change CD8 expression. Nevertheless, the HBV-specific CTLs can be deleted or dysfunctional or succumb to exhaustion in patients with chronic HBV infection ( Benechet and Iannacone, 2017 , Kawashima et al., 2018 ). Moreover, recent studies showed that priming by hepatocytes, CD8 + T cells differentiated into dysfunctional HBV-specific CTLs, with partial overlap with those of exhausted or tolerant T cells; thus, these HBV-specific CTLs could not be rescued by treatment with immune checkpoint inhibitors such as anti-PDL1 or CD40-mediated myeloid dendritic cells (mDCs)-activation ( Benechet et al., 2019 , Isogawa et al., 2013 ).…”
Section: Limitationsmentioning
confidence: 99%